An experience of simulation of union representation and collective bargaining - R. Galindo Caldés (Universitat Politècnica de València, 2019)
Simulation is a teaching methodology of great possibilities in university teaching, especially in subjects that allow the reproduction of situations that can occur in a real environment. This essay describes a simulation experience in union representation and collective bargaining in the teaching of civil service law, analysing the impact and effects on three fundamental aspects: motivation, cooperation and learning. Specifically, we describe the planning and implementation of a simulation in a classroom of the degree of labour relations, with the participation of 62 students. It is proposed to the participants the reproduction of an Administration in which all of them are civil servants. Therefore, they must exercise their collective rights, which imply the holding of elections, the constitution of union representation bodies and the negotiation of working conditions with the Administration. In this sense, the format and method of assessment of the second continuous assessment test is subject under discussion. Through this experience we can observe very positive aspects: the fact that simulation is perceived as a motivating activity, that encourages cooperation among students and that has contributed to better results in regard to the assimilation of the contents of the teaching plan. Despite the difficulty of its implementation, it is a very useful teaching methodology with great potential for its use in the classroom.